العنوان (مصطلح الساعة في القران الكريم (دراسة تحليلية نقدية) - فهد حيدر خزعل (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
It highlights the concept of the Qur’an, interprets some of the specific criteria for understanding the Qur’an and non-arbitrariness in the interpretation, and works to show the semantic evolution of the Qur’an, which is the evolution that makes us independent of others in explaining the meanings of the words and phrases in it. And did you act on the formulation of this in a methodological proposal that confirms the structure of the divine text? Al-Qur’anic words are used as semantic units in this text. And this is the verbal entry for understanding, which is the basis for starting the interpretation of the entire text. The executive level is now based on the cases of the Qur’anic word, because the Qur’anic meanings will be represented by all the cases, and the linguistic context will be subject to the attributes of the denotative word. And so, it is a way to discover all the qualities that are hidden in the language. And the context in Manhajna, the extended context goes beyond the one position to all the positions of the word, and this extends to the direction of unity of signification without multiplicity. And words from the cases of use, from the semantic determinants of the word, the place of study, and the accompanying words. I have monitored the search for the word "hour", and focused on the synthetic relationships of attribution, belonging, addition, addition, etc. And the result of this is that the name of the hour is associated with the verbs al-Majji, al-Ityan, and al-Qiyam, and the hour can be seen with the eyes of the al-Majij, and it is an object in the world, and there is a question and fear of things, it is a matter of punishment, and there is no room for fleeing or delaying. With other attributes, it is confirmed that they are wise by having the ability to plan through transition, surprise, and choosing the right time; It comes upon the differences of the parties between them, and so it is my list of the names of the resurrection, as the commentators see.